Risk Based Audit oleh Satuan Kerja Audit Intern pada PT. Bank JAT - Devi Afifah Sukmawardhani Achmad (Jurnal Ekonomi Akuntansi dan Manajemen, 2018)
Based on Indonesia Bank Regulation Number 11/25/PBI/2009 about changes to the regulations of Bank of Indonesia Number 5/8/PBI/2003 which requires commercial banks in Indonesia to apply risk management in banking activities. The regulation requires banks indirectly push the activity of the audit process by applying risk-based Internal Audit (Risk Based Audit). Risk Based Audit is the audit that focused and prioritized in areas of high risk business segment. Implementation of Risk Based Auditing Standards refer to the Implementation of Internal Audit Function (SPFAIB) issued by Bank Indonesia and the Internal Audit Charter PT. Bank JAT. This reasearch aims to determine and evaluate the implementation of Risk Based Audit conducted by the Internal Audit Division (IAD) PT. Bank JAT is already in accordance with the standards of Bank Indonesia. Evaluation is conduct by distributing questionnaires to the Internal Audit Division (IAD) for the position, qualifications, work planning, risk assessment, and implementation of Risk Based Audit by the Internal Audit Division (IAD). Based on the evaluationl results of the implementation of Risk Based Audit in PT. Bank JAT, it can be concluded that the implementation has been in accordance with SPFAIB. Expected implementation of the Risk Based Audit is able to minimize the risk and incidence of irregularities that occurred in the activity of PT. Bank JAT. Keywords: Risk Based Audit, Internal Audit Division (IAD)